Cover Feature: Tandem In Situ Monitoring for Quantitative Assessment of Mechanochemical Reactions Involving Structurally Unknown Phases (Chem. Eur. J. 56/2017). Issue 56 (10th August 2017) - Lukin, Stipe; Stolar, Tomislav; Tireli, Martina; Blanco, Maria Valeria; Babić, Darko; Friščić, Tomislav; Užarević, Krunoslav; Halasz, Ivan
Abstract : Raman spectroscopy and powder X‐ray diffraction probe the mechanochemical reaction in tandem and in situ, each providing complementary information on the reaction course and insight into reaction mechanism. Both can quantitatively evaluate reaction profiles, and Raman spectroscopy—even in situations when powder diffraction fails. This cover art was made by Perica Matijević, academy‐trained sculptor. It represents a glimpse to the dark side of the reaction vessel enabled by the two techniques used in tandem. More information can be found in the Full Paper by K. Užarević, I. Halasz et al. onpage 13941 .